Administration of Mung Bean Extract (Phaseolus radiatus) in Increasing Hb and Ferritin Level and Decreasing Malondyaldehide (MDA) Level in Anaemic Rats - Heni Wijayanti (Universitas Sultan Agung Semarang, 2018)
BACKGROUND: Mung bean, not only contains protein, carbohydrates, and fats, but also contains iron and vitamin C which are proven to overcome anemia in pregnant woman. High iron levels are potential to increase ROS production through fenton reaction.